Pericapsular Nerve Group Block for Prosthetic Hip Reduction in the Emergency Department: Case Report - Rebecca Thomas; Matthew Carr; Janae Fry; Taryn Hoffman (Clinical Practice and Cases in Emergency Medicine)
Introduction: A pericapsular nerve group (PENG) block is unique compared to other regional anesthetic techniques (femoral nerve and fascia iliaca blocks) because it is a motor-sparing block. It also provides anesthesia to more nerves that innervate the anterior capsule of the femoroacetabular joint when compared to the femoral nerve and fascia iliaca blocks. Additionally, regional anesthesia carries fewer risks and requires less resources when compared with procedural sedation, which is the typical method for reducing a dislocated femoroacetabular joint. Case Report: We describe a novel case in which a PENG block was used in the emergency department (ED) to reduce a prosthetic hip dislocation. Conclusion: The PENG block is a safe and effective method of achieving sufficient analgesia to reduce prosthetic hips in the ED.